2D flood modeling using PCSWMM - Arti Dhananjay Gulwadi. (2013)
This project investigates a relatively new software, PCSWMM 2D, for the computational hydraulic modeling of systems. In addition to the usual 1D functionality that is offered by the EPA SWMM, this software can model 2D free surface flow, while still using the 1D Saint Venant equations. The 2D characteristics are defined by an underlying Digital Elevation Model layer designed using ArcGIS. The different functions in PCSWMM 2D were explored and used during the course of this project. In order to check the accuracy of the software, an artificial catchment whose observed hydrograph values were already known, was modeled on PCSWMM 2D. The resulting simulated values were then compared with the observed one. The result proved that discretizing the catchment area into a greater number of subcatchments increased the accuracy of the results. PCSWMM 2D works on the principle of discretizing the catchment into a very large number of cells or subcatchments. For instance, the catchment modeled in the following report consisted of approximately 4500 subcatchments. These discretized subcatchments are well connected by conduits. As a result, the 2D model resulted in a solution very close to the observed hydrograph. On calibration using the Nash-Sutcliffe coefficient method, the 2D simulation provided an average of 90% similarity compared to the observed. The following project proved that the 2D version has many advantages; it is easy to use and provides largely accurate results. However, a few limitations were noticed especially in terms of loss estimation. In SWMM, losses cannot be accounted for in open channel flow, and the 2D SWMM layers are all modeled as open channels.